RERATA PERBANDINGAN EKSPRESI PROTEIN Bax DAN Bak PADA PREEKLAMPSIA BERAT DAN KEHAMILAN NORMOTENSI - , Tejo Sujatmiko ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Preeclampsia is still become major cause of maternal and perinatal mortality. The placenta is an important and central focus on the pathogenesis of preeclampsia. Failure of trophoblast cells perform remodeling on spiral arteries due to excessive apoptosis causes uteroplacental ischemia and endothelial cells damage, that induce clinical manifestations of preeclampsia especially through the intrinsic pathway in which intracellular Bax and Bak are genes that play a role as a cells apoptosis regulator ( as pro-apoptosis ). They are located in the mitochondria and endoplasmic reticulum activates caspase to regulate the intrinsic apoptotic pathway that subsequently activates caspase cascade resulting in cell death processes. Objective: Comparing the mean of Bax and Bak protein expression between normotensive pregnancies and severe preeclampsia. Methods: This research is a cross-sectional study design with a sample of severe preeclampsia and normotensive patients who were treated at RSUP dr . Sardjito Jogjakarta between October 2011 to March 2012, with total patients of 81. Observation of Bak and Bax protein expression by immunohistochemistry techniques. Results: The mean expression of Bax and Bak proteins in severe preeclampsia group higher and statistically significant compared to normotensive group. Difference that demonstrated significant statistically (p <0.05), with a mean value Bax expression 0,23 (CI 95 % 0,12 - 0,34) and the mean expression of Bak 0,44 (95 % CI 0,10 - 0,78). Conclusion: Expression of Bax and Bak proteins in severe preeclampsia is higher than normotensive pregnancies and Bax protein statistically moretake effect in preeclampsia compared to Bak protein